The Anthropic Cosmological Principle: A Thematic Case of Teleology and Causality in Contemporary Science - Barbosa, João (2022)
The successive versions of the anthropic cosmological principle reintroduced teleology in cosmology, articulating it with two forms of mechanical causality – probabilism and determinism. According to the thematic analysis of science proposed by Gerald Holton, we can say that teleology is the opposing thema (the antithema) of mechanical causality. A return of teleology easily creates suspicions because mechanical causality dominates contemporary science, and teleology is widely considered an obsolete kind of scientific reasoning. Furthermore, in the anthropic cosmological principle, teleology has a deep anthropocentric feature. From the thematic point of view, the teleology of the anthropic cosmological principle is in counter-cycle. However, the cyclical functioning of themata suggests that perhaps teleology is not forever condemned to the past or to a marginal presence in scientific thought.